DINAMIKA RESELLER PADA ONLINE SHOP JAM TANGAN JURAGAN7AM - Puji Lestari Reski Fitriani; Mohamad Dimyati; Imam Suroso (RELASI : JURNAL EKONOMI, 2018)
A significant increase in internet usage provides a great opportunity for online business activists. According to a survey in 2016 there are 132.7 million Indonesians are connected to the internet of a total population of 256.2 million people, with a percentage of 77% of the amounts that do online shopping. Increasing the number of internet users it also affects the online shop juragan7am, which is growing. This research is a qualitative research with phenomenology model. The selection of informants using non-random-sampling or nonprobability sampling method of 9 informants. Sampling technique used is Accidental Sampling technique. The result of this research is motivation of entrepreneur become motivation which is informant as a reseller. Price and marketing media has no influence on the dynamics of reseller that occurs in online shop juragan7am. Keywords: reseller, motivation, online shop, entrepreneur, phenomenology.